Applied process thought. - Dibben, Mark R.; Newton, Rebecca (Process thought, 2009)
Concentrating mainly on the process philosophy developed by Alfred North Whitehead, this series of essays brings together some of the newest developments in the application of process thinking to the physical and social sciences. These essays, by established scholars in the field, demonstrate how a wider and deeper understanding of the world can be obtained using process philosophical concepts, how the distortions and blockages inevitably inherent in substantivist talk can be set aside, and how new and fertile lines of research in the sciences can be opened as a result.